Assessment of degradation and biocompatibility of electrodeposited chitosan and chitosan–carbon nanotube tubular implants. Issue 11 (5th July 2016) - Nawrotek, Katarzyna; Tylman, Michał; Decherchi, Patrick; Marqueste, Tanguy; Rudnicka, Karolina; Gatkowska, Justyna; Wieczorek, Marek
Abstract: Designing three‐dimensional tubular materials made of chitosan is still a challenging task. Availability of such forms is highly desired by tissue engineering, especially peripheral nerve tissue engineering. Aiming at this problem, we use an electrodeposition phenomenon in order to obtain chitosan and chitosan–carbon nanotube hydrogel tubular implants. The in vitro biocompatibility of the fabricated structures is assessed using a mouse hippocampal cell line (mHippoE‐18). As both implants do not induce significant cytotoxicity, they are next subjected to in vitro degradation studies in the environment simulating in vivo conditions for specified periods of time: 7, 14, and 28 days. The mass loss of implants indicates their stability at the tested time period; therefore, the materials are subcutaneously implanted in Sprague Dawley rats. The explants are collected after 7, 14, and 28 days. The assessment of composition and changes in tissues surrounding the implanted materials is made in respect to surrounding tissue thickness as well as the number of blood vessels, macrophages, lymphocytes, and neutrophils. No symptoms of acute inflammation are noticed at any point in time. The observed regular healing process allows concluding that both chitosan and chitosan–carbon hydrogel tubular implants are biocompatible with high application potential in tissue engineering. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 2701–2711, 2016.